Wood destroying fungi in residential construction / Fatin Ruzanna Jamaluddin - Jamaluddin, Fatin Ruzanna (2004)
The wood destroying fungi in residential constructions appear the problem in building and any construction and can cause high destruction or damages of wood buildings for example in wood framing, beam, column and other wood products. The problem of dry rot in buildings engaged the attention of architects and builders from the beginning of the nineteenth century onwards, and became increasingly serious as oak was gradually replaced by softwoods for buildings purposes. It is no less serious a problem today. Decay of timber was studied in the first instance by men who were primarily forest pathologists interested mainly in disease of growing trees. The association between fungi and decay in timber was noticed many centuries ago.